Reduction in Hindquarter Vascular Resistance Supports 5-HT7 Receptor Mediated Hypotension - Seitz, Bridget M.; Watts, Stephanie W.; Fink, Gregory D. (Frontiers in Physiology, 2021)
The 5-HT7 receptor is the primary mediator of both the acute (< hours) and chronic (day-week) falls in mean arterial pressure (MAP) during low dose 5-HT infusion in rats. Previous data shows the fall in MAP during chronic infusion of 5-HT is due to a decrease total peripheral resistance (TPR) and specifically splanchnic vascular resistance. We hypothesized that changes in vascular resistance in both the splanchnic and skeletal muscle vascular beds are critical to the cardiovascular effects mediated by the 5-HT7 receptor. Systemic and regional hemodynamic data were collected in conscious and anesthetized male rats using radiotelemetry, vascular catheters and transit-time flowmetry. Reversible antagonism of the 5-HT7 receptor was achieved with the selective antagonist SB269970 (33 g/kg, iv). From the very beginning and throughout the duration (up to 5 days) of a low dose (25 g/kg) infusion of 5-HT, TPR and MAP were decreased while cardiac output (CO) was increased. In a separate group of rats, the contribution of the 5-HT7 receptor in the regional hemodynamic response was tested during 5-HT-induced hypertension. The decrease in MAP after 24 hour of 5-HT (saline 833 vs 5-HT 703 mmHg) was associated with a significant decrease in skeletal muscle vascular resistance (saline 60.2 vs 5-HT 40.4 mmHg/min/mL) while splanchnic arterial resistance was similar in 5-HT and saline-treated rats. When SB269970 was administered acutely, MAP and skeletal muscle vascular resistance rapidly increased, whereas splanchnic resistance was unaffected. Our work suggest the most prominent regional hemodynamic response to 5-HT7 receptor activation paralleling the fall in MAP is a decrease in skeletal muscle vascular resistance.